EFEKTIVITAS PELATIHAN APLIKASI MENDELEY TERHADAP KUALITAS SITASI KARYA ILMIAH CALON GURU SEKOLAH DASAR - Trivena; Reni Lolotandung; Lutma Ranta Allo Linggi; Yohanis Padallingan; Hakpantria; Weryanti Laen Langi; Roberto Salu Situru; Rasnita Dewi (STKIP Subang, 2026)
Training on the use of the Mendeley application is one strategy to enhance the skills of prospective elementary school teachers in citing sources, managing references, and accessing reputable scientific articles. This study employed an intervention design with a post-test only approach to assess the effectiveness of the training. The activity was conducted as a short workshop lasting four hours, using a hands-on learning method, and was attended by 40 students. The training materials included an introduction to Mendeley and its functions, application installation, citation techniques, searching for scientific articles in reputable national and international journals, and managing both physical and digital references. Post-test results showed that 85% of students understood the principles of correct citation, 90% were able to use Mendeley to manage references, 80% could independently search for reputable scientific articles, and all participants demonstrated improved technological literacy and practical skills. Analysis indicated that the hands-on learning approach was effective in enhancing students’ academic skills, in accordance with the Information Literacy Framework and Cognitive Load theory. This training provides a strong foundation for prospective teachers to produce quality scientific papers and improve digital literacy. The findings also offer recommendations for the development of more comprehensive Mendeley-based training and future research using experimental designs and long-term evaluation